2017
DOI: 10.1039/c6ra28633j
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide nanoparticles dispersed in Pluronic F127 hydrogel: potential uses in topical applications

Abstract: The present study is focused on the synthesis and characterization of nitric oxide (NO)-releasing superparamagnetic iron oxide nanoparticles, and their incorporation in Pluronic F127 hydrogel with great potential for topical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 63 publications
5
33
1
Order By: Relevance
“…The O 1s deconvoluted XPS spectra shows two types of oxygen present in the IONPs (Figure B). This confirms that iron oxide is in form of Fe 3 O 4 …”
Section: Resultssupporting
confidence: 74%
“…The O 1s deconvoluted XPS spectra shows two types of oxygen present in the IONPs (Figure B). This confirms that iron oxide is in form of Fe 3 O 4 …”
Section: Resultssupporting
confidence: 74%
“…Permeation study carried using a Strat-M™ membrane demonstrated that the iron will not permeate from the nanoparticle dispersed in Pluronic. [111] Topical delivery of niclosamide (niclo) using octenylsuccinate hydroxypropyl phytoglycogen (OHPP) as a solubilizing agent.…”
Section: Study Important Findings Referencesmentioning
confidence: 99%
“…The first one is, the presence of another diamagnetic layer besides the chitosan; and the second one is the contributions from intrinsic particles, shape and stress anisotropies due to different ligands along with interparticle interactions (dipolar), which can provide a difference in the energy barrier. Nanoparticles are strongly attracted by a magnetic field, and when this field is removed, their magnetization is reduced close to zero, without residual magnetization [54][55][56]. Figure 6a shows SEM images for nanoparticles containing IBU, in which the light green dots corresponds to iron (Fe, from magnetite core), dark green corresponds to oxygen (O, from magnetite, chitosan and ibuprofen) and red dots correspond to carbon (C, from chitosan and ibuprofen) atoms.…”
Section: Magnetic Measurementsmentioning
confidence: 99%